“Diffused Geoparks”: Territorial Integration as Solution for a Shared Sustainable Growth Based on Geotourism in Italy, Japan and Tunisia - Roberta Varriale; Laura Genovese; Barbara Aldighieri (Heritage, 2022)
The concept of a UNESCO Global Geopark (UGGp) itself implies that the integration of geological, biological and anthropogenic factors and related values, both tangible and intangible, are at the base of any interpretation, communication, educative practices and enhancement aiming at strengthening the sense of place in local communities, as well as guiding those areas toward sustainable economic growth. However, the measures and good practices codified for UGGps limit their impact on the properties’ boundaries, sometimes neglecting the strong natural, social and cultural link between the listed areas, their surroundings and other serial geosites. The paper introduces a five-step study on selected examples of Geoparks and geosites in Italy, Japan and Tunisia, sometimes also including areas inscribed in the UNESCO list as cultural sites, focusing on the possible role of UGGps as drivers for sustainable development of geotourism. The research considers the contextualization of UNESCO UGGps within a broader territorial scale, introducing the concept of Diffused Geopark as a new opportunity in protection and management practices and as a driver for local economies and internationalization of lesser-known contexts.